2009
DOI: 10.2514/1.37697
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Stability and Accuracy for Weighted Essentially Nonoscillatory Scheme

Abstract: This paper studies the weights stability and accuracy of the implicit fifth-order weighted essentially nonoscillatory finite difference scheme. It is observed that the weights of the Jiang-Shu weighted essentially nonoscillatory scheme oscillate even for smooth flows. An increased " value of 10 2 is suggested for the weighted essentially nonoscillatory smoothness factors, which removes the weights oscillation and significantly improves the accuracy of the weights and solution convergence. With the improved " v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 31 publications
(47 reference statements)
0
117
0
Order By: Relevance
“…In their paper [53], e is taken as 10 À6 . In [54], Shen et al suggested to use an optimized e value of 10 À2 in the smoothness estimators to achieve optimal weight in smooth regions in order to minimize dissipation and improve convergence.…”
Section: High Order Weno Reconstruction [53]mentioning
confidence: 99%
“…In their paper [53], e is taken as 10 À6 . In [54], Shen et al suggested to use an optimized e value of 10 À2 in the smoothness estimators to achieve optimal weight in smooth regions in order to minimize dissipation and improve convergence.…”
Section: High Order Weno Reconstruction [53]mentioning
confidence: 99%
“…In this paper, at boundaries, the conservative variables are first obtained using various required boundary conditions [43], and then the primitive variables used in preconditioning system are calculated from the conservation variables accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [43], the e value of 10 À2 suggested by Shen et al to suppress the oscillation of IS k and improve the convergence and accuracy is adopted in this paper. The q R is constructed symmetrically as q L about i + 1/2.…”
Section: The Weno Reconstructionmentioning
confidence: 99%
“…They introduced fourth-order fluxes to overcome this drawback. For transonic flows, Shen et al [14] suggested to use an optimized ε in the smoothness estimators to achieve optimal weight in smooth regions in order to minimize dissipation. A class of higher than 5th order weighted essentially non-oscillatory schemes are designed by Balsara and Shu in [15].…”
Section: Introductionmentioning
confidence: 99%
“…The implicit time marching method with unfactored Gauss-Seidel line relaxation is used with the 5th order WENO finite difference scheme described in [14] for solving the Navier-Stokes equations. The viscous terms are discretized using the 4th order conservative central differencing suggested by Shen and Zha [17].…”
Section: Introductionmentioning
confidence: 99%